A study of a fatty acids C16-C18 distillation tower accident through leakage cause analysis with a fire scenario construction approach. (December 2022) - Zhang, Xiaoliang; Tao, Guangyuan; Wang, Haobo; Xie, Yufei; Liang, Fanjie; Ben, Fang; Zhao, Yanli
Highlights: Combined with traditional accident investigation and numerical simulation, the process of accident occurrence and development is reconstructed. The corrosion forms and causes of the failed pipelines were determined by means of macro analysis, micro analysis and chemical composition analysis. The corrosion rate of pipeline is estimated and the mechanism of pipeline corrosion is presented. Abstract: A fire accident caused by corrosion leakage of fatty acid pipeline is being investigated. The occurrence and development of leakage and fire are reconstructed through numerical simulation. The total heat release rate of the fire is estimated to be 81.411 MW through leakage amount and on-site fire damage, and the fire scale is determined to be intermediate. In addition, the corrosion site is determined to be the weld junction between the original pipe and the replacement pipe using macroscopic analysis, scanning electron microscopy and energy spectrum analysis, metallographic analysis, and chemical composition analysis. The main reasons for the corrosion are the uniform corrosion and pitting corrosion perforation of the weld caused by the different materials of the new pipe and the original pipe. The internal and external pressure difference of the pipe in service directly leads to the damage and failure of the weak weld.